Kinerja Keuangan Berbasis Economic Value Added pada PT. Kimia Farma Tbk - Mursidi, La Ode Kamaludin; Sumantri, Sri (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the financial performance of PT. Kimia Farma, Tbk using the Economic Value Added (EVA) approach as a measurement tool for creating economic value. EVA, calculated as the difference between Net Operating Profit After Tax (NOPAT) and Weighted Average Cost of Capital (WACC), is used to assess the efficiency of the company's capital management. The research data were derived from the company's financial statements for the period 2019–2023, using descriptive quantitative analysis techniques. The results indicate that over five years, EVA at PT. Kimia Farma, Tbk consistently showed negative values. This condition was caused by the increase in capital costs (WACC), largely influenced by the high proportion of debt-based financing compared to equity, as well as negative fluctuations in NOPAT. In 2023, EVA reached its lowest point at Rp-2,999,101,780, reflecting capital costs disproportionate to the company's operational performance. This study highlights the importance of restructuring the capital structure to reduce reliance on debt, improving operational efficiency to boost NOPAT, and prioritizing investments that yield returns exceeding the WACC.